Influence of the Novel Histamine H3 Receptor Antagonist/Inverse Agonist M39 on Gastroprotection and PGE2 Production Induced by (R)-Alpha-Methylhistamine in C57BL/6 Mice - Bastaki, Salim M. A.; Amir, Naheed; Więcek, Małgorzata; Kieć-Kononowicz, Katarzyna; Sadek, Bassem (Frontiers in Pharmacology, 2019)
The role of histamine H3 receptors (H3Rs) in the regulation of gastroprotection and production of prostaglandin E2 (PGE2) as well as somatostatin remains contradictory. Therefore, the effects of the H3R antagonist/inverse agonist M39 on in vivo acidified ethanol-induced gastric ulcers and gastric acid secretion in the C57BL/6 mice were assessed. Results showed that acute systemic administration of H3R agonist (R)-α-methylhistamine (RAMH, 100 mg/kg, i.g.) significantly reduced the severity of ulcer index, increased gastric acid output, and increased mucosal PGE2 production without any alteration of somatostatin concentration in gastric juice. However, only acute systemic administration of the H2R agonist dimaprit (DIM, 10 mg/kg, p.o.) significantly decreased the level of somatostatin measured in gastric juice. Moreover, acute systemic administration of M39 (0.3 mg/kg, i.g.) abrogated the RAMH-induced increase of acid output as well as PGE2 production, but not the DIM (10 mg/kg, i.g.)-stimulated acid secretion, indicating that RAMH as well as M39 modulate the gastroprotective effects through interactions with histamine H3Rs. The present findings indicate that agonistic interaction with H3Rs is profoundly involved in the maintenance of gastric mucosal integrity by modulating PGE2 as well as gastric acid secretion, with no apparent role in the regulation of the inhibitory influence of somatostatin.